Economic Growth Effects of Fiscal Policy in South Africa: Empirical Evidence from Personal Income Tax - Tala, Lavisa (International Journal of Economics and Financial Issues, 2024)
This study determined economic growth effects of fiscal policy in South Africa. Particular attention was paid to effects of personal income tax on economic growth for the period 1993Q3 -2022Q4. The influence of personal income tax on economic growth was analysed using non-linear autoregressive distributed lag (NARDL) bounds test for cointegration. Estimated results indicated rise in personal income tax is growth-friendly in the short-run. While, in the long –run growth is affected by both positive and negative shocks in personal income tax. Positive personal income tax changes are detrimental to economic growth in the long run. Increasing personal income tax will compromise the country’s economic growth strategy. Furthermore, positive changes in personal income tax affect economic growth more than negative shocks as confirmed by dynamic multiplier graph. Dynamic multiplier graph further reveal existence of asymmetry. Additionally, Wald test value of -6.2775 validated asymmetric effect of personal income tax on economic growth. It is therefore, recommended that policy makers should focus on considering other sources of tax revenue. The current structure of the tax system is skewed towards personal income tax. Policy makers should keep the current ratio of personal income tax and widen tax base to realise inclusive economic growth.